Metafora dalam Qosidah Nahdiyyah Satu Abad Nahdlatul Ulama: Resepsi Sastra Wolfgang Iser - Umam, Syarifudin Choirul; Amsariah, Siti; Yuningsih, Yeni Ratna (Journal of Linguistics and Social Studies, 2025)
Qasidah Nahdliyah Satu Abad NU (QNSANU) is a literary work composed by KH. Afifudin Muhajir to commemorate the centennial of Nahdlatul Ulama (NU). According to Iser, no literary work holds complete meaning if it remains static as a document; it must be read and actively responded to by readers. Authors deliberately leave gaps or empty spaces within the text as a platform for readers to engage their imagination, leading to multiple interpretations that enrich perspectives and understanding of the literary work. This study aims to examine how these gaps are filled by respondents or readers, thereby revealing diverse interpretations. The research employs a qualitative method, with metaphor data collected through an experimental approach, involving fieldwork and interviews with 11 master's students of Arabic Language and Literature from the Faculty of Adab and Humanities, UIN Syarif Hidayatullah Jakarta, Class of 2024. The study emphasizes that the second stanza of Qasidah Nahdliyah Satu Abad NU possesses significant symbolic power in establishing both emotional and intellectual connections with its readers. The findings support the hypothesis that the qasidah serves as an effective aesthetic medium for representing NU's historical, spiritual, and ideological values. Metaphors in the stanza, such as kaukabah (star) and al-barq fi al-zulma (lightning in the darkness), successfully create a framework for diverse interpretations depending on the readers' backgrounds. These interpretations demonstrate the qasidah's ability to bridge multiple perspectives, both among individuals directly connected to NU and those with no direct affiliation.